Intrathecal antibody production against Epstein-Barr and other neurotropic viruses in pediatric and adult onset multiple sclerosis - Pohl, Daniela; Rostasy, Kevin; Jacobi, Christian; Lange, Peter; Nau, Roland; Krone, Bernd; Hanefeld, Folker (Journal of neurology, 2010)
Epstein-Barr virus (EBV) has been implicated in the pathogenesis of multiple sclerosis (MS). Recent reports proposed an increased EBV-targeted humoral immune response in MS, which appears to be more pronounced in pediatric patients. However, little is known about the CNS-derived antibody production against EBV in patients with MS. The objective of this study was to assess the frequency and intensity of intrathecal antibody production against EBV as compared to other neurotropic viruses in pediatric and adult onset MS. In cohorts of 43 childhood, 50 adult onset MS patients, 20 children and 12 adults with other CNS disorders, paired CSF and serum samples were studied. Frequency and intensity of intrathecal antibody production against EBV as compared to measles, rubella, varicella zoster (VZV) and herpes simplex virus (HSV) were analyzed by determination of virus-specific CSF-to-serum Antibody Indices (AI). Intrathecally synthesized EBV antibodies were detectable in 26% pediatric and 10% adult onset MS patients, compared to frequencies ranging in both groups from 10 to 60% for the other viruses. Median AIs for EBV were lower than those for all other viruses, with more than twofold higher median AI for measles, rubella and VZV. The EBV-targeted humoral immune response in the CNS is only part of the intrathecal polyspecific antibody production in MS, directed against various neurotropic viruses. Our results do not rule out the possibility that EBV is involved in the pathogenesis of MS by triggering diverse cellular immune mechanisms, but they argue against a direct pathogenic role of EBV-targeted humoral immune response within the CNS.
Online veröffentlicht: 28. August 2009
Gesehen am 04.05.2023